2023
DOI: 10.1073/pnas.2221542120
|View full text |Cite
|
Sign up to set email alerts
|

Application of a quantitative framework to improve the accuracy of a bacterial infection model

Abstract: Laboratory models are critical to basic and translational microbiology research. Models serve multiple purposes, from providing tractable systems to study cell biology to allowing the investigation of inaccessible clinical and environmental ecosystems. Although there is a recognized need for improved model systems, there is a gap in rational approaches to accomplish this goal. We recently developed a framework for assessing the accuracy of microbial models by quantifying how closely each gene is expressed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Utilizing an existing data set of P . aeruginosa transcriptional profiles in expectorated sputum [ 64 ], we found that all of the kdp genes are expressed during infection in people with CF ( Fig 7A ). We went on to determine whether these genes are conserved in clinical isolates of P .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Utilizing an existing data set of P . aeruginosa transcriptional profiles in expectorated sputum [ 64 ], we found that all of the kdp genes are expressed during infection in people with CF ( Fig 7A ). We went on to determine whether these genes are conserved in clinical isolates of P .…”
Section: Resultsmentioning
confidence: 96%
“…Kdp gene expression was assessed using previously reported data set of RNAseq data from recently expectorated P . aeruginosa from CF patients [ 64 ]. Multisequence alignment was performed on all of the Kdp proteins’ amino acid sequences using genomes for PAO1, PA14, and 8 clinical isolates from patients with CF acquired from the NCBI Genome Database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultracentrifugation eliminated microbial contaminants, insoluble aggregated mucin polymers, and other debris, while preserving intact soluble mucins. Dialysis serves to equilibrate salt and metal concentrations, which have been previously reported to affect P. aeruginosa behavior and antimicrobial efficacy ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating the effect of airway mucus polymers on bacterial behaviors have traditionally relied on: laboratory media, focused on the presence or absence of mucus polymers ( 56 ), and/or utilized non-biological polymers, such as polyethylene glycol ( 57 ) or agar gels ( 58 ). Using synthetic CF sputum medium (SCFM2), a well-characterized and chemically defined in vitro CF mucus simulant ( 50 52 , 54 ), as a starting point, we investigated the contribution of increasing concentrations of mucin and eDNA to antipseudomonal antibiotic efficacy.…”
Section: Introductionmentioning
confidence: 99%